Analisis Kemampuan Pemecahan Masalah Siswa Pada Materi Usaha dan Energi Berdasarkan Tahapan Polya: Studi Kasus Di Madrasah Aliyah Kabupaten Sumbawa - Hermansyah Hermansyah; Adelliya Tusandini; Armansyah Putra (Fakultas Keguruan dan Ilmu Pendidikan Universitas Samawa, 2026)
This study aims to analyze the problem-solving ability of grade X students at an Islamic senior high school (Madrasah Aliyah) in Sumbawa Regency on the topic of Work and Energy using George Polya's four problem-solving stages: variable identification, concept selection, mathematical execution, and result verification. Data were collected through a test administered to 11 students, interviews with the subject teacher, and observation of classroom conditions and school facilities. The results show that the class average score was only 42.27, far below the Minimum Mastery Criteria (KKM) of 70-75, with a 0% pass rate. The most prominent weaknesses were found in the mathematical execution and result verification stages, while variable identification was relatively better mastered, although often incomplete. Further analysis indicates that difficulty increases with the complexity of the problem-solving steps, particularly in conceptual-narrative and multi-step problems. The main contributing factors include weak prerequisite mathematical knowledge, low science literacy, limited variation in teaching methods (dominance of lecturing), and restricted access to instructional media and laboratory facilities. These findings suggest the implementation of Problem Based Learning (PBL) supported by educational game media as an alternative strategy to train problem identification skills while increasing students' motivation to learn physics.